CURRENT METHODS OF ENDOTHELIAL DYSFUNCTION ASSESSMENT AND THEIR POSSIBLE USE IN THE PRACTICAL MEDICINE - A. V. Shabrov; A. G. Apresyan; A. L. Dobkes; S. U. Ermolov; T. V. Ermolova; S. G. Manasyan; S. V. Serdyukov (Столичная издательская компания, 2017)
A review contains a description of the most common methods of evaluation and monitoring of "endothelial dysfunction" that are assessed in terms of their information content and applicability in the practice of medicine. The term "endothelial function" is interpreted primarily as a function of the regulation of capillary blood flow, carried out by the expense of the dynamic change of the phase of vasoconstriction and vasodilatation in vessels of resistive type (in accordance with the changing needs of cellular metabolism). Assessment of endothelial dysfunction is understood as a generalized indicator of the extent and nature of violations of the regulation of peripheral circulation. It includes an assessment of imbalances between endotheliumdependent vasoconstrictor and vasodilating factors or mismatch of the local and central regulation of capillary blood flow in response to various functional tests or other effects (eg, cold test, or test with local ischemia). All methods of endothelial dysfunction assessment in the survey are divided into invasive and non-invasive. The main feature of invasive methods lies in the direct effect on the endothelium of the coronary or other vessels by introducing into these vessels vasoactive substances such as acetylcholine. Response to the test (vasoconstriction or vasodilation) is evaluated by coronary angiography or by ultrasound. Non-invasive methods of the assessment of endothelial dysfunction or functions of regulation of the peripheral circulation are regarded as the most promising for widespread use. There are two basic methods that underlie functional tests: methods PAT (peripheral arterial tone) and PHG (polyhepatography). Assessment of endothelial dysfunction in many modern scientific researches is important. They are regarded as the causative factors of many different diseases. Such assessments can be useful in everyday medical practice. Assessment of endothelial function provides the clinician with critical information essential for a personalized selection of therapy. In particular, for taking into account the individual characteristics of the local and central regulatory system response of peripheral blood circulation in the various functional tests, or other effects.